Tourism Impact Analysis on Danish Regions - Jie Zhang (European Regional Science Association (ERSA), 2001)
LINE model is an interregional macroeconomic model describing the economy of the 275 Danish municipalities. Tourism sub-model is an integrated part of LINE model, where tourism data are built in as a part of private consumption. The purpose of building tourism sub-model within the LINE model is to integrate tourism data into this interregional economic model. Hence, the tourism demand is not only an exogenous variable to the model, but endogenous one, which will depend on the changes in disposable income of the population, price of tourism products and transport, etc. LINE model is constructed based on SAM i.e. Social Accounting Matrix, therefore, tourism impact analysis based on this model will provide more information concerning economic analysis. The first part of the paper gives a brief introduction to the structure of LINE model and the links between the LINE and the tourism sub-model. The second part of the paper concentrates on tourism impact analysis. Tourism demand by Danish regions is shown here, which is based on a large tourist survey in Denmark. Tourism impact analysis is presented based on the different scenarios. These scenarios are set up in consideration of both tourist demand and regional development strategies. Hence, the regional consequences of tourism development reflect the regional policy.
Keywords: 330